Highly Efficient Photoacoustic Conversion by Facilitated Heat Transfer in Ultrathin Metal Film Sandwiched by Polymer Layers. Issue 2 (5th October 2016) - Lee, Taehwa; Guo, L. Jay
Abstract : Photoacoustic (PA) conversion of metal film absorbers is known to be inefficient because of their low thermal expansion and high optical reflection, as compared to polymeric materials containing light absorbing fillers. Here, highly efficient PA conversion is demonstrated in metal films. By using a metal film absorber sandwiched by transparent polymer layers, PA conversion is significantly enhanced, which is even comparable to in the highest reported in the CNT‐polymer composites. Such enhancement is accomplished by ultrathin metal film (10 nm) capable of facilitating heat transfer to the adjacent polymers having high thermal expansion coefficient. This thin metal layer also allows integration of a photonic resonance cavity, effectively compensating the potential absorption loss of the thin metal. This strategy allows for easy spatial PA signal patterns and high conversion efficiency, which not only can be implemented for deep tissue PA imaging of implants or tools, but also provides a guideline for designing photoacoustic transmitters and contrast agents. Abstract : Enhanced photoacoustic conversion in thin metal film sandwiched by polymer layers is demonstrated by taking advantage of both facilitated heat transfer and photonic resonance. The metal film (10 nm) integrated to a photonic resonance cavity can absorb up to 90% of incident light that is converted to heat, and also facilitate heat dissipation to surrounding polymers having high thermal expansion properties.